Achieving scale collectively - Bassi, Vittorio; Muoio, Raffaela; Porzio, Tommaso; Sen, Ritwika; Tugume, Esau (National Bureau of Economic Research, 2024)
This cross-sectional assessment surveyed 1,115 firms and 2,883 employees between 2018 and 2019 in the Central, Western, and Eastern regions of Uganda to understand the importance of the rental market to productivity in developing countries. It argues that rental market interactions allow small firms to increase their effective scale and mechanize production, even when each individual firm would be too small to invest in expensive machines. An equilibrium model of firm behavior was built and estimated with the data. Findings show that once accounted for rental market interactions, the average firm size increased by 77%, from 5 to 8.8 employees, and the share of firms with more than 10 employees increased from 5% to 33%. These findings speak to the importance of rental markets for the mechanization and productivity of small firms. This paper shows, the rental market shapes the effectiveness of policies to foster mechanization, such as subsidies to purchase machines.